2015
DOI: 10.1542/peds.2014-4073
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Use During Pregnancy and Asthma in the Offspring

Abstract: BACKGROUND AND OBJECTIVES: It has been suggested that maternal depression during pregnancy is associated with asthma in the offspring, but the role of medical treatment of depression is not known. Our goal was to examine whether prenatal antidepressant use increases the risk of asthma in the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
5
12
0
Order By: Relevance
“…No experimental studies were found; therefore only analytical epidemiological studies were included, which comprised of 27 cohort studies, two case-control studies, and one cross-sectional study. The type of psychosocial stress indicators investigated in the studies included anxiety, [21][22][23][24]27,30,35,36,48,49 depression, [22][23][24]30,35,37,41,42 bereavemet, 29,32,38 work-related stress, 33,36,47,48 and NLEs, 19,20,25,26,28,31,34,39,40,[43][44][45][46]49,50 which were usually comprised of a composite of different indicators of stressors. Most studies assessed maternal stress using self-completed validated questionnaire; in a few studies maternal stress was assessed from population registers, particularly stress resulting from bereavement of a family member.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…No experimental studies were found; therefore only analytical epidemiological studies were included, which comprised of 27 cohort studies, two case-control studies, and one cross-sectional study. The type of psychosocial stress indicators investigated in the studies included anxiety, [21][22][23][24]27,30,35,36,48,49 depression, [22][23][24]30,35,37,41,42 bereavemet, 29,32,38 work-related stress, 33,36,47,48 and NLEs, 19,20,25,26,28,31,34,39,40,[43][44][45][46]49,50 which were usually comprised of a composite of different indicators of stressors. Most studies assessed maternal stress using self-completed validated questionnaire; in a few studies maternal stress was assessed from population registers, particularly stress resulting from bereavement of a family member.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most studies assessed maternal stress using self-completed validated questionnaire; in a few studies maternal stress was assessed from population registers, particularly stress resulting from bereavement of a family member. Twelve studies assessed the impact of maternal stress on asthma, 20,[27][28][29][30][31][32]34,37,38,42,46 eight studies on atopic eczema/dermatitis, [22][23][24]28,31,44,47,48 ten studies on wheeze, 20,[24][25][26][27][28]30,35,42,43,46 three studies on allergic rhinitis, 24,28,31 three on atopic sensitization, 27,31,42 and six studies on cord blood IgE or cytokines 19,21,36,39,45,50 (Table S1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Researchers may need to study meta-analysis inclusion criteria to ensure that their studies can be included in meta-analyses. However, some of the inclusion criteria such as randomization may not be feasible because of the inherent difficulty of random assignment for this research including the ethical problems of assignment to anti-depressant vs. untreated groups and to therapy versus non-therapy groups [80]. Waitlist control groups are not an option because of cohort effects (different gestational age).…”
Section: Limitations Of This Recent Literaturementioning
confidence: 99%
“…Previous studies mostly evaluated single measures or a limited number of measures of psychosocial stress or stress correlates (e.g., psychological functioning), including maternal negative life events ( 1 , 4 , 7 , 11 , 15 ), depression/anxiety ( 3 , 6 , 12 , 14 , 16 ), community violence ( 2 ), bereavement ( 5 , 8 , 13 ), job strain ( 9 ), and demoralization ( 10 ). These studies also varied in the outcome definition, where some evaluated wheezing symptoms ( 2 , 10 12 , 15 ) and others evaluated asthma ( 1 , 3 9 , 13 , 14 ). Furthermore, most of these studies relied on maternal reporting of childhood asthma, while only a few used information from national registries/administrative databases ( 5 , 8 , 13 , 14 ).…”
mentioning
confidence: 99%
“…These studies also varied in the outcome definition, where some evaluated wheezing symptoms ( 2 , 10 12 , 15 ) and others evaluated asthma ( 1 , 3 9 , 13 , 14 ). Furthermore, most of these studies relied on maternal reporting of childhood asthma, while only a few used information from national registries/administrative databases ( 5 , 8 , 13 , 14 ).…”
mentioning
confidence: 99%